Impact Analysis of Webqual, Price And E-Wom on Return Stay Intention of Hotel Guests - Fendry Palijama (IJBAMS: International Journal of Business Accounting Management Social Science, 2026)
For decades, information technology has played a crucial role in transforming and developing the hospitality and tourism industries. The emergence of e-commerce websites has created new, potentially powerful communication and distribution channels for hotels, narrowing the gap between hotels and consumers. While the internet and the hospitality industry are widely recognized, hotels need to understand the importance of website quality in shaping customer behavior. In the hospitality context, repurchase intention refers to a guest's intention to stay at the same hotel again in the future. Repurchase intention is crucial for hotels, and is shaped by website quality, price, and e-WOM. The purpose of this study is to analyze the influence of WebQual, price, and e-WOM on repurchase intentions. This study is a survey, a quantitative study using structured or systematic questions to respondents. All answers are then recorded, processed, and analyzed. Respondents in this study were 200 guests of star-rated hotels who had stayed at at least one of the star-rated hotels in Batu City, Malang. The results showed that WebQual, price, and e-WOM significantly influenced repurchase intention. WebQual was the most influential factor in repurchase intention. Practical recommendations include improving website quality, adopting competitive pricing policies, managing eWOM reviews and government support to support the hospitality industry in enhancing the tourist appeal of the area.